Thermodynamics and Equilibria in Earth System Sciences: An Introduction - Middelburg, Jack J. (SpringerBriefs in Earth System Sciences, 2024)
Thermodynamics is needed to understand many processes on Earth, be they physical, chemical, or biological. Thermodynamics is critical to study the atmosphere (lapse rate, fohn winds, circulation), hydrosphere (latent and sensible heat, pressure dependence of freezing/boiling points), geosphere (geothermal gradients, mineral stability) and the biosphere (redox zonation, evolution of biogeochemical cycles). This introduction to thermodynamics and equilibria aims to provide the basic concepts of relevance for atmospheric, marine, climate, and environmental sciences and to prepare students for more advanced classes in physical chemistry, mineralogy, and petrology. This is an open access book.